Culture, convention, and continuity: Islam and family firm ethical behavior. Issue 2 (15th January 2021) - Alrubaishi, Dalal; McAdam, Maura; Harrison, Richard
Abstract: Although some scholarly attention has been devoted to the role of religion in entrepreneurship, there is a scarcity of research that focuses on the influence of Islam in the family business domain in general and the impact of Islamic concepts on the ethical behavior of Muslim family firms in particular. In addressing this, we reveal how the founder's ethical behavior which is informed by the Islamic concepts tawakkul, taqwa, honesty, and dignity is imprinted as values onto next‐generation leaders through mentoring, role modeling, and job shadowing, and thus embedded at the family firm level. We conceptualize these insights through the development of a formal framework for the analysis of the imprinting of Islamic influences on family firm ethical behavior. In addressing the roots of ethical behavior, we make contributions to the family business, Islamic entrepreneurship, and imprinting literatures. In practical terms, we highlight the importance of informal practices in endorsing the ethical behavior of the next‐generation family members.